The Geminid meteor shower during the ECOMA sounding rocket campaign: Specular and head echo radar observations - Stober, G.; Schult, C.; Baumann, C.; Latteck, R.; Rapp, M. (Göttingen : Copernicus, 2013)
The ECOMA (Existence of Charge state Of meteoric smoke particles in the Middle Atmosphere) sounding rocket campaign was conducted during the Geminid meteor shower in December 2010 in order to explore whether there is a change of the properties of meteoric smoke particles due to the stream. In parallel to the rocket flights, three radars monitored the Geminid activity located at the launch site in Northern Norway and in Northern Germany to gain information about the meteor flux into the atmosphere. The results presented here are based on specular meteor radar observations measuring the radiant position, the velocity and the meteor flux into the atmosphere during the Geminids. Further, the MAARSY (Middle Atmosphere Alomar Radar System) radar was operated to conduct meteor head echo experiments. The interferometric capabilities of MAARSY permit measuring the meteor trajectories within the radar beam and to determine the source radiant and geocentric meteor velocity, as well as to compute the meteor orbit. publishedVersion